Determinants of puerperal sepsis among post partum women at public hospitals in west SHOA zone Oromia regional STATE, Ethiopia (institution BASEDCASE control study) - Getu Alemu Demisse; Samuel Dessau Sifer; Buseraseman Kedir; Daniel Belema Fekene; Gizachew Abdissa Bulto (BMC, 2019)
Abstract Background Puerperal sepsis is an infection of the genital tract, which occurs from rupture of amniotic sacs and within 42ndday after delivery. It happens mainly after discharge in the 1st 24 h of parturition. It is the third leading cause of direct maternal mortality in developing nations. It is also among preventable conditions. Even though multiple interventions were done to overcome these health problems, maternal mortality and morbidities were still significant. Mainly, in Ethiopia lack of clearly identified causes of maternal mortality and morbidity makes the problem unsolved. Methods Case-control study was conducted at public Hospitals in west shoa zone Oromia regional state, Ethiopia from February 01 to April 30/2018.women with puerperal sepsis (n = 67) were selected by convenience method. Controls (n = 213) were selected by systematic random sampling. Controls to cases ratio was 3:1 and structured questionnaire was used to interviewafter verbal consent was obtained. Data was entered in to epi -info 7.2 then exported to SPSS version 20.0 for analysis. A logistic regression model was used for data analysis. Those variables which have p-value < 0.05 were accepted that they are independent determinants of puerperal sepsis. Result Rural residence (AOR [95%CI] = 2.5(1.029-6.054),Mothers with no formal education (AOR [95%CI] = 6.74([1.210-37.541]), up to primary level of education(AOR [95%CI] = 6.72(1.323-34.086), total monthly income of the mother or family<=500 ETB and 501-1500 ETB(AOR [95%CI] = 5.94(1.471-23.93) and (AOR [95%CI] =6.57 (1.338-32.265) respectively, Mothers having 1-2 times antenatal care(ANC)visit (AOR [95%CI] = 6.57([1.338-32.265]), Duration of Labor12-24 h (AOR [95%CI] = 3.12 (1.805-12.115),> = 25 h (AOR [95%CI] = 4.71([1.257-17.687]),vaginal examinations > = 5times (AOR [95%CI] = 4.00([1.330-12.029]), Delivery by C/S (AOR [95%CI] = 3.85 ([1.425-10.413]), Rupture of membrane > 24 h (AOR [95%CI] = 3.73([1.365-10.208]) and those Referred from other health institutions (AOR [95%CI] = 2.53([1.087-5.884],were independent determinants of puerperal sepsis in this study. Conclusion Majority of determinants of puerperal sepsis were related with pregnancy and childbirth. Therefore, to tackle a problem of puerperal sepsis all concerning bodies should take measures during prenatal, natal and postnatal period.